The Use of Wellness Tourism in Tourism Development: A Case Study in Baluwarti Village, Surakarta City - Made Prasta Yostitia Pradipta (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
The development of the Covid-19 pandemic has temporarily halted the tourism service business in Surakarta, leading to the emergence of policies regarding tourist attractions and objects. The research was conducted in the Baluwarti Tourism Village, which offers health tour packages to help tourists maintain their mental and physical health during the pandemic. As a result, tourism service businesses are developing alternative tourism options such as wellness or health tourism that can combine tourism and health. Data was collected through library or library research methods and analyzed by selecting, processing, and grouping the data to make it more concise. The findings revealed that the most popular tourist objects and attractions in Surakarta were artificial and cultural attractions, with the majority of them being artificial museums. The study also found several rare tourist attractions such as the "Walking Tour Royal Wellness Tourism" tour package, Javanese Cooking Class, Dance/Gamelan Learning, Constructing Janur, Using Javanese Language, and Making Traditional Herbs/Helpers. This alternative tourism is expected to contribute to the development of tourism in Surakarta, allowing tourists to stay longer in the city with additional tour packages.